Answer:
Option C is correct.
The equation can become [tex]4x-12-5x -5 = 3[/tex] by applying distributive property.
Step-by-step explanation:
Given an equation: [tex]4(x-3)-5(x+1) = 3[/tex]
Distributive property states that when a number is multiplied by the sum of two numbers, then the first number can be distributed to both of those numbers and multiplied by each of them separately i.e,,
[tex]a \cdot(b+c) = a\cdot b +a\cdot c[/tex]
Apply distributive to the given equation we get;
[tex]4 \cdot x -4\cdot 3-5\cdot x -5 \cdot 1 =3[/tex]
Simplify:
[tex]4x-12 -5x -5 = 3[/tex]
Therefore, the statement which shows a correct next step in solving the equation is, the equation can become [tex]4x-12 -5x -5 = 3[/tex] by applying distributive property.